Gaya Komunikasi Sutradara Dalam Proses Pembuatan Film Joko Songo Di Bakar Production - Amara, Ayunita Rizky; Riyanto, Buddy (Solidaritas, 2024)
Communication style impacts a person’s relationships, both in their career and personal social life, and also affects emotional well-being. It enables individuals to work on aspects that may be considered either good or bad. Communication style can observe and follow various events that occur between people through various media, including in the success of a film production. The film Joko Songo is a fictional film produced by Bakar Production and directed by Dwi Mustanto. The production process of Joko Songo is interesting because most of those involved, including the director, did not come from a filmmaking background. This research can also serve as evidence that communication style plays a crucial role in the creative process, particularly in filmmaking. The research in this thesis uses descriptive research with a qualitative method. This qualitative descriptive method has natural characteristics, meaning it is developed based on real conditions in the field. The sampling technique in this research uses purposive sampling (judgmental sampling). Purposive sampling is a sampling method used by researchers by considering the characteristics of the audience that have been previously identified. Based on the research findings, the director used the open communication style from Norton’s theory. Through this open communication style, the director exhibited different characteristics but had a positive impact that helped improve the director’s performance in the filmmaking process. Keywords: Communication Style, Director, Film Joko Songo.